Marginal basins of the NW Pacific and Eastern Eurasia. Issue 7 (23rd May 2020) - Ding, Weiwei; Sun, Zhen
ABSTRACT: The broad zone between old oceanic lithosphere of the NW Pacific and Eastern Eurasian continental lithosphere is home to a chain of marginal basins. Different from oceans, marginal basins are more influenced by the underlying subduction zone both geophysically and geochemically and are more likely to be blanketed by sediments from the nearby continent. This special issue collects 19 papers that explore the tectonic, magmatic, sedimentary and fluid activity features of marginal basins during rifting, spreading and post-spreading stages. Most papers in this special issue focus on South China Sea marginal basins, where abundant research provides interesting insights into how marginal sea basins evolve. Because South China Sea basins are fully evolved and their key features have not been overprinted by younger deformation, the results of this special issue are very useful for understanding the evolution of other marginal basins.